Microscopical Study of Pancreatic Tissue of Babirusa (Babyrousa babyrussa) Using Conventional and Immunohistochemical Methods - Ketut Mudite Adnyane; Alastair A Macdonald; Srihadi Agungpriyono (Universitas Syiah Kuala, 2010)
This study utilized conventional and immunohistochemical methods, to describe the morphology and distribution of glucagon and insulin cells in the pancreas of adult male babirusa (Babyrousa babyrussa). The results of research showed that the endocrine portion (Langerhans islet) spread evenly on the acinar portion of pancreas. Observation using immunohistochemical method showed that glucagon cells were distributed on the perifer, whereas insulin cells in the center of the Langerhans islet of pancreas. In general, the number of insulin cells was higher than glucagon cells. It is interesting to note, in the pancreas babirusa also found that neonatal elements similar to the Langerhans islet, but have larger sizes (ranging between 200 -700 mm). The picture is similar to the large Langerhans islet was reported in ruminant. These cells give a negative reaction to insulin and glucagon antisera.